Respuesta :

Answer:

Step-by-step explanation:

-5(y-15=3x) = -5y+75=-15x

add 15x to both sides and subtract 75 to both side

-5y+15x=-75

5y-2x=-3

13x=-78

and then both side divide by 13

x=-6

y-15=3(-6)

y-15=-18

Y= (-18) - 15 =  -3

y=-3

and the answer will be  (-6,-3)

hope that help you

Space

Answer:

(-6, -3)

General Formulas and Concepts:

Pre-Algebra

Order of Operations: BPEMDAS

  1. Brackets
  2. Parenthesis
  3. Exponents
  4. Multiplication
  5. Division
  6. Addition
  7. Subtraction
  • Left to Right

Equality Properties

Algebra I

  • Solving systems of equations using substitution/elimination
  • Solving systems of equations by graphing

Step-by-step explanation:

Step 1: Define Systems

y - 15 = 3x

-2x + 5y = -3

Step 2: Rewrite Systems

y - 15 = 3x

  1. Add 15 to both sides:                    y = 3x + 15

Step 3: Redefine Systems

y = 3x + 15

-2x + 5y = -3

Step 4: Solve for x

Substitution

  1. Substitute in y:                         -2x + 5(3x + 15) = -3
  2. Distribute 5:                              -2x + 15x + 75 = -3
  3. Combine like terms:                13x + 75 = -3
  4. Isolate x term:                          13x = -78
  5. Isolate x:                                   x = -6

Step 5: Solve for y

  1. Define equation:                    y - 15 = 3x
  2. Substitute in x:                       y - 15 = 3(-6)
  3. Multiply:                                  y - 15 = -18
  4. Isolate y:                                 y = -3

Step 6: Graph Systems

Check the solution set.

Ver imagen Space